THE CAUSES OF MILITARY INTERVENTIONS IN POLITICS: A CASE STUDY OF PAKISTAN AND BANGLADESH - Muhammad Dawood (European Scientific Journal, ESJ, 2014)
Military in Pakistan and Bangladesh has been deeply involved in politics all over the history. Since after the birth of both countries, the strong democratic government has not yet been established, due to the continuous involvement of Military in politics. The current research attempts to evaluate the main causes of Military Intervention in two countries. The utilized information of causes has been taken from books, journals, articles, on line materials and other secondary sources. The findings result with regard to the sources of military interventions in politics are the causes of weak political institution, vested interest of the military, legacy of the British army, political corruption and superiority.